Penyuluhan Anti-Korupsi dalam Upaya Meningkatkan Integritas dan Transparansi di Indonesia - Yuyut Prayuti; Lasmin Alfies Sihombing; Yeni Nuraeni (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
In an effort to tackle corruption that impedes Indonesia's social and economic progress, this service project focuses on the effectiveness of anti-corruption counseling to increase integrity and transparency among students, education personnel, and the community. Using Service Learning methodology, this activity involves counseling integrated in the learning process and community service delivery, with the cooperation of the West Java High Prosecutor's Office to ensure the relevance of the material. Results showed an increase in participants' awareness and competence in identifying and countering corruption, with 85% reporting increased capacity. The outreach also successfully promoted a culture of integrity and triggered local initiatives for greater transparency in resource management, strengthening the legal and institutional framework through policy advocacy. The findings support the need for expansion of similar programs and increased collaboration between sectors to strengthen corruption eradication efforts in Indonesia.